1995
DOI: 10.1111/j.1365-2265.1995.tb00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and the pituitary‐thyroid axis status in blind adults: a possible resetting after puberty

Abstract: A possible resetting of pituitary-thyroid axis regulation can occur in blindness after puberty; variations of melatonin secretion could play a role in this. The inhibitory effect of melatonin on thyroid gland function found in animals does not seem to occur in humans. Elevated melatonin levels, both in patients with total blindness and in those with light perception only, suggest that more complex mechanisms other than light signalling are involved in the changes of melatonin secretion in blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This is supported by evidence of increased inflammation and reduced melatonin levels in schizophrenia patients (Anderson and Maes, 2012; Muller et al, 2012). Conversely, blind individuals have elevated melatonin levels (Bellastella et al, 1995), which has been shown to attenuate cognitive impairments (Peck et al, 2004) and reduce inflammation (Cuzzocrea et al, 1999; Sharma et al, 2012). Another potential mechanism involves cortical thickness and pruning.…”
Section: Mediating Biological Variablesmentioning
confidence: 99%
“…This is supported by evidence of increased inflammation and reduced melatonin levels in schizophrenia patients (Anderson and Maes, 2012; Muller et al, 2012). Conversely, blind individuals have elevated melatonin levels (Bellastella et al, 1995), which has been shown to attenuate cognitive impairments (Peck et al, 2004) and reduce inflammation (Cuzzocrea et al, 1999; Sharma et al, 2012). Another potential mechanism involves cortical thickness and pruning.…”
Section: Mediating Biological Variablesmentioning
confidence: 99%
“…Thus, it seems that in blind individuals with a retained circadian rhythm, the latter light perception system has a special significance. The inhibition of melatonine secretion under the influence of light impulse originating in the outer environment, even in individuals lacking light perception, allows as a result for the acceleration of puberty processes [BELLASTELLA et al 1995].…”
Section: Resultsmentioning
confidence: 99%
“…This influences menarche because melatonin overproduction is related with late menarche so people exposed to reduced sunlight hours could suffer a late sexual maturation. 47 Melatonin acts on gonads and reduces gonadotropin secretion, which retards the development of menarche in women and would prolong exposure to scoliosis-causative factors. 48 In the same line, visual impairments such as blindness would also affect menarche as the malfunctioning of the visual system would reduce the quantity of light that the subject would receive and, therefore, increase melatonin production.…”
Section: Summary Of Findingsmentioning
confidence: 99%